Analisis Pengaruh Fraksi Berat Pengisi Komposit PANi/n-SiO2 terhadap Sifat Elektrokimia dengan Metode Polarisasi Potensiodinamik - Pratama, Dian Sandi; Lazuardi Akmal Islami; Dani Mardiyana; Dwi Mardika Lestari (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
The study of the effect of the weight fraction of the filler on the PANi/n-SiO2 composite was carried out in a high salinity medium. Nanosilica (n-SiO2) was synthesized from amorphous silica coprecipitation of Bancar Tuban natural sand using calcination method at 900oC for 6 hours. The synthesized nanosilica was mixed with paint using a variation of filler weight 0.25; 0.5; and 0.75 grams, then coated on SS304 steel. Corrosion experiments consist of two methods, namely polarization to determine the corrosion rate and immersion to identify corrosion products. The experimental results show that the PS50 sample has the lowest rate of 1.04x10-5 mpy